Digital media: theory and practice - Tileubay, Т.; Sauyrbaeva, Ә.Ж. (Bulletin of L.N. Gumilyov Eurasian National University. JOURNALISM Series, 2021)
The article aims to describe features of modern digital technology, which have brought great changes to the media industry in recent years. It also aims to determine a direction of media development. There are systematized and analyzed views and positions of domestic and foreign theorists and practitioners on the theory and practice of digital media. It also considers a process of adaptation of the classic both domestic and foreign media to digital media and changes in journalists’ work and professional ethics in the digital era. The article does not examine digital technology exclusively as a factor in media development. There is a need to reconsider some issues in the field of journalism. There is emphasized a need to become a professional journalist. Media technology is considered as sort of art, and the transformation of professionalism is a natural phenomenon. In this regard, the article provides a foreign experience in the field of journalism as an example. The author’s point of view is based on the assumptions about the breathing of classical media in the digital age. Based on results of the study and statistics, the author argues that despite the pessimistic forecasts, there are prospects for the development of newspapers and magazines. It is necessary to adjust strategies that will allow to operate successfully in the digital age and gain new positions to solve the problem of their adaptation to new conditions. The modern nature of new media is based on the theory and practice of analyzing the transformation of information communications in the digital age.